Does diffusion-weighted MRI (DW-MRI) change treatment strategy in pediatric cholesteatoma?. (May 2012) - Koitschev, Assen; Behringer, Pia; Bögner, Dorothee; Amrhein, Peter; Winkler, Peter; Kalle, Thekla von
Abstract Conclusion: This review highlights the currently limited and contradictory evidence on the role of diffusion-weighted magnetic resonance imaging (DW-MRI) in the management of pediatric cholesteatoma patients. Available data confirm the need for prospective DW-MRI studies of a larger number of pediatric patients. Factors such as patient compliance, adhesion to follow-up or local logistic circumstances should also be considered. Objectives: This systematic review aimed to collect and analyze the body of evidence on the usefulness of DW-MRI in first-stage tympanoplasty and in replacing second-look surgery in children with cholesteatoma. Methods: A comprehensive search of medical databases was conducted. The keywords used were pediatric/paediatric, magnetic resonance imaging, MRI, DW-MRI, cholesteatoma, child, and all meaningful combinations of them. Results: Only one study with 17 patients primarily fulfilled all criteria. Sensitivity, specificity, and positive and negative predictive values were 62%, 88%, 89%, and 58%, respectively. A second study retrospectively analyzed a subset of younger patients (n = 21) of a larger population. Sensitivity, specificity, and positive and negative predictive values were 100%. One additional study described 1 child and 11 adolescents among 32 cases. In all cases the correlation between imaging and surgery findings was 100%. There were no randomized controlled trials and power calculations were not performed.